Formulasi Dan Evaluasi Sedian Tablet Dengan Metode Kempa Langsung - Aura Nasyafa; Novita Indira Sari; Lili Sa’adah; Nur Asyifa Ramadhanti; Tiara Maulida (CV. ITTC INDONESIA, 2024)
The objective of this research is to study the formulation and evaluation of tablet preparations using the direct compression method. The method used in this research is a Systematic Literature Review. The findings of the study explain that the direct compression method is an efficient and economical technique in tablet production, especially in the pharmaceutical industry. With the advancement of technology, this method is increasingly used to produce tablets directly from a mixture of active ingredients and excipients without going through granulation processes, whether wet or dry. This process allows for time and cost savings in production, as well as reducing the use of machinery and labor. The main advantage of direct compression is its ability to produce tablets with better disintegration and dissolution times, especially for active ingredients sensitive to heat and moisture. The selection of the appropriate fillers and binders, such as modified starch, pregelatinized potato starch, and Avicel, significantly impacts the physical quality of the tablets, including hardness, friability, and flowability. Furthermore, the research results show that the correct formulation, both in terms of the composition of excipients and the concentration of binders, can improve the physical properties of the tablets and meet the desired quality standards. Therefore, while the direct compression method offers many advantages, it is important to continue exploring and optimizing formulations, both in terms of excipient selection and mixing ratios, to achieve tablets with the best quality that meet pharmaceutical needs and are accepted by consumers.